Paket Wisata Bagi Difabel Di Yogyakarta - Febri Handoyo; Aufi Nidau Sholihah; Anggit Novitariasari; Ashila Fitra Hani; Qonita Putri Firdausa; Handayani Rahayuningsih (Jurnal Pariwisata Terapan, 2017)
Yogyakarta is the one of the biggest tourist destination in Indonesia. Domestic and Foreigner tourist come to this city every year in big number. Yogyakarta has so many tourist destinations, for example: Keraon Yogyakarta, Sambisari Temple, Taman Pintar, Malioboro, etc. Because of that, Yogyakarta need travel agents to makes every tourist easier enjoy their trip, and the number of travel agents in Yogyakarta has growth every year. Tourist who come to Yogyakarta is not only normal people, but also people with disability, they also have same chance to do tourism activity and travel agents should accommodate it. The purpose of the research is to know how far the travel agents in Special Region of Yogyakarta can create tour package for people with disabilities. The research also explained about how many local tourists and international tourists who come to Yogyakarta every year. From that data, we know how many markets for tour package in Yogyakarta. The methods used in the research is qualitative method. The writers collected the data by interview, literature study, and observation. The subject of the interview is people with disability, government, and the management of the tourism destination. The writers also compare the result from the interview with the fact in the field. From the result of the research the writers can conclude tour package that has been offered by travel agents in Yogyakarta is not friendly for people with disabilities.